2019
DOI: 10.1002/pssa.201800986
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Kinetics of the Interstitial Carbon–Dioxygen Complex in Silicon

Abstract: The interstitial carbon-interstitial dioxygen complex (C i O 2i ) has a deep state close to the mid bandgap of Si and can be an efficient recombination center. In this work, the annealing kinetics of C i O 2i in p-type, boron doped, Czochralski grown (Cz) silicon are studied. Two sets of samples are irradiated at room temperature (RT) with 1.8 MeV protons to doses of 1 Â 10 13 cm À2 (set A) and 5 Â 10 13 cm À2 (set B). After irradiation, the samples of both sets are pre-annealed at 400 C for 30 h in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 18 publications
4
14
0
Order By: Relevance
“…These conclusions are in agreement with previous PL and DLTS measurements referring to the investigation of the C i O 2i defect [18,19]. It was suggested that the annealing of the C i O i occurs via dissociation into C i and O i , where a percentage of the released C i atoms are trapped by oxygen dimers to form the C i O 2i [17,18].…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…These conclusions are in agreement with previous PL and DLTS measurements referring to the investigation of the C i O 2i defect [18,19]. It was suggested that the annealing of the C i O i occurs via dissociation into C i and O i , where a percentage of the released C i atoms are trapped by oxygen dimers to form the C i O 2i [17,18].…”
Section: Introductionsupporting
confidence: 92%
“…This might result in more stable defects, which may need a higher temperature to anneal out. Additionally, the detected signal in our IR studies could refer to different states of the same defect reported in previous photoluminescence (PL) and DLTS measurements [17][18][19]. Further clarification of this issue requires future work.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations